THE RELATIONSHIP BETWEEN SHIP CREW PROFESSIONALISM AND THE IMPROVMENT OF PASSENGER SATISFACTION ON KM. PANGRANGO - Michelle Leony Seran; Faisal Saransi; Fajrur Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between ship crew professionalism and the improvement of passenger satisfaction on KM. Pangrango PT. PELNI. The research method used is quantitative with an explanatory approach. The research population is KM. Pangrango passengers with a sample of 350 respondents taken using accidental sampling technique. Data collection techniques used a Likert scale questionnaire. Data analysis was performed using simple linear regression with SPSS 25. The results showed that the research instrument was valid with r-count 0.681-0.782 > 0.105 and reliable with Cronbach's Alpha 0.913 for variable X and 0.904 for variable Y. The classical assumption test was met with normally distributed data Sig. 0.200, linear Sig. 0.000, and free from heteroscedasticity Sig. 0.305. The results of the regression analysis show that there is a positive and significant relationship between ship crew professionalism and the improvement of passenger satisfaction with a correlation coefficient value r=0.712, coefficient of determination R²=0.508, t-count=18.938 > t-table=1.967, and Sig. 0.000 < 0.05. This means that 50.8% of the improvement in passenger satisfaction is influenced by ship crew professionalism, while 49.2% is influenced by other factors. PT. PELNI is advised to maintain the professionalism of the ship crew and improve other service aspects.